Localised querying and location update service in wireless sensor and robot networks with arbitrary topology. (2016) - Lukic, Milan; Mezei, Ivan
In a typical wireless sensor and robot networks (WSRN) setup, sensor nodes detect events which require response from mobile robots. First, a static information structure is established in the network, allowing an event-detecting node to send a request to a nearby robot, to visit its location. The movement of the robots imposes changes in the network structure, which are handled in location update process. These protocols should perform in a localised, distance-sensitive, energy efficient manner. Here we present a new protocol based on localised formation of Voronoi cells (vCell), and compare it with existing protocols (Quorum and iMesh) in dense networks, sparse networks, and networks with holes in topology. We also present location update algorithms which deal with robot mobility. Our simulations show that vCell achieves nearly 100% success rate in finding the nearest robot in dense networks. In sparse networks, it outperforms the other existing solutions by up to 40%.